Sustainable Challenges: Community Response to the Policy Restricting the Use of Plastic Shopping Bags in Jambi City - Fadillah, Nisaul; Reza, Muhammad; Ardi, Unggul Suryo (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2024)
This research investigates the issue of plastic waste in Jambi City by exploring the cognitive (knowledge), affective (emotional support), and conative (attitudinal support) aspects of the community towards the policy of restricting the use of plastic shopping bags. Through a survey method involving 86 respondents from the community of Jambi City, the study evaluates the people's understanding of plastic waste and the level of emotional support for plastic reduction policies and attitudes towards reducing plastic waste. The research reveals a high level of knowledge (77.78%) and significant emotional support (71.05%) for the policy of limiting plastic use in Kota Jambi, while attitudinal support for reducing plastic waste is also high (74.96%). These findings underscore the importance of community awareness and support for measures to reduce single-use plastic consumption, along with significant implications for waste management and environmental conservation in Kota Jambi.